Cytopenias in Various Combinations Found in Routine Complete Blood Counts - Nadeem Nusrat, Farah Fatima Abbas, Muhammed Akbar Agha, Rabiyah Nadeem, Aslam Kkan, Saima Minhas, Saddam Hussain Kalwar, Zaen elabdeon Pahore, Bippin Nepal, Asma Shaikh , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To identify the type and frequency ofdifferent cytopenias in our laboratory Study Design: Retrospective/observational. Place & Duration: Dr. Ishrat-ul-Ebad Khan Institute of Blood Diseases (DIEKIBD). Dow University offlealth Sciences, Karachi, Pakistan, from April 2013 to June 2013. Material & Methods: Cytopenias either alone or in various combinations were identified on routine complete blood counts from the records of all CBC performed during the said period. Results: Two thousands samples were analyzed, 313 ( 15.65 %) had cytopenias either alone or in combination. 232 (74.12 % ) had isolated single or mono cytopenia, 60 (19.17 % ) had bicytopenia & 21 (6.71 %) had pancytopenia. Conclusion: There is significant occurrence of cytopenias either alone or in combinations and it needs immediate reporting of peripheral smear morphology. These cases should be immediately communicated to the relevant physician for proper further investigations, so that complications of underlying disease can be prevented